Sie sind auf Seite 1von 13

x 2 + 7x + c = 0.

1

0 = x 2 7x c = x 2 7x +

2

7

2

2 7 2 2 c = x 7

2

2

2

7

2

2 2 c.

49

4

+ c = x 7

2

2

.

0 x

< c

1

49

> c 49

4

= c 49

4

4

x 1,2 = 7

2

±

49

4

+ c

D = 49 + 4c D < 0

49 + 4c < 0 c < 49

4

x 2 + 7x + c = 0 c c = 10 > 49

4

x 1,2 = 7

2

±

49

4

10 = 7 ± 9

4

2

10
y
x
2 4
6
8
−10
−x 2 + 7x − 10

x 1 = 2 x 2 = 5 c = 49

4

x 1,2 = 7
2 ,
10
y
x
2 4
6
8
−10
−20
−x 2 + 7x − 49
4

c = 16 < 49 x 2 + 7x 16 = 0

4

10
y
x
2 4
6
8
−10
−20
−x 2 + 7x − 16

x 2 + ax + 1 = 0

x 1,2 = a

2

± a 4 2 1.

1

D < 0 |a| < 2 D = 0 a = ±2 D > 0 |a| > 2 x 2 + ax + 1 = 0 a a = 4 < 2

D = a 2

4

x 1,2 = 2 ± 4 1 = 2 ± 3

x 1 = 2 3 x 2 = 2 + 3

10
y
5
x
2
4

x 2 4x + 1

c = 2

x 1,2 = 1,

10
y
8
6
4
2
x
−2
2
4

x 2 2x + 1

c = 0 x 2 + 1 = 0

10
y
8
6
4
2
x
−2
2

x 2 + 1

n = 0, 1, 2, 3, 4 a n

a 0 = 0 = 0

a 1 = 1 = 1

a 2 = 2

a 3 = 3

a 4 = 4 = 2

b n

b 0 =

1

1 + 0 = 1

b 1 =

1 + 1 = 1

2

1

b 2 =

1 + 2 = 1

3

1

b 3 =

c n

0

c 0 = (1) 0 2 + 0 = 0

c 3 = (1) 3

3

2 + 3 = 5

3

c 1 = (1) 1

1

2 + 1 = 3

1

c 4 = (1) 4

4

2 + 4 = 2

3 .

1

1 + 3 =

1

4

c 2 = (1) 2

b 4 =

1

1 + 4 = 5

1

2

2 + 2 =

1

2

3

a 0 = a 0

a 1 = 3a 0

a 2 = 3a 1 = 3 · 3a 0 = 3 2 a 0

a 3 = 3a 2 = 3 · 3 2 a 0 = 3 3 a 0

a 4 = 3a 3 = 3 · 3 3 a 0 = 3 4 a 0 .

a n = 3 n a 0 , n 0 .

b 0 = b 0

b 1 = 3b 0 + 2

b

3b 2

b 4 = 3b 3

b

+ 2

3b 1 + 2

3(3b 0 + 2) + 2 = 3 2 b 0 + 2 · 3 + 2 = 3 2 b 0 + 2(3 + 1)

2

3

=

=

=

=

3(3 2 b 0

+ 2 = 3(3 3 b 0

+ 2(3 + 1)) + 2 = 3 3 b 0 + 2(3 2 + 3 + 1) + 2(3 2 + 3 + 1)) + 2 = 3 4 b 0 + 2(3 3 + 3 2 + 3 + 1).

b n = 3 n + 2(3 n1 +

+ 1) = 3 n b 0 + 2

n1

k=0

3 k .

n1

k=0

x k = 1 + x + x 2 + ··· + x n1 = 1 x n

1 x ,

b n = 3 n b 0 + 2 1 2 3 n = 3 n b 0 1 + 3 n = 3 n (b 0 + 1) 1.

a n

1, 4, 9, 16, 25,

a n = n 2

a n

a n

= 1 + 3 + 5 + · · · + (2n 1) = (1 + 0) + (1 + 2) + (1 + 4) + · · · + (1 + (2n 2))

n

= n + 2 + 4 + · · · + 2(n 1) = n + 2(1 + 2 + · · · + n 1) = n + 2b n1

= n + 2 (n 1)n

= n + (n 1)n = n(1 + n 1) = n 2

2

a n = n 2

b n

 2b n · · · (n − 2) (n − 1) (n − 1) (n − 2) · · ·

2 n (n + 1)

b n = n(n + 1)

2

.

A(n) a n = n 2 n

n 0 = 1

1 2 = 1 = a 1 ,

A(1)

n A(n)

a n+1 = 1 + 3 + ··· + 2n 1 +(2(n + 1) 1) = a n + 2n + 1 = n 2 + 2n + 1 = (n + 1) 2 .

=a n

A(n + 1) A n

c n

1,

5,

12, 22,

35, 51,

70, 92, 117,

.

.

.

 1, 1 · 5, 2 2 · 3, 2 · 11, 5 · 7, 3 · 17, 2 · 5 · 7, 2 2 · 23, 3 2 · 13, . 1 · 2 2 · 5 , 3 · 8 , 4 · 11 , 5 · 14 , 6 · 17 , 7 · 20 , 8 · 23 , 9 · 26 2 , 2 2 2 2 2 2 2 2 ,

c n = n(3n1)

2

.

.

.

.

.

c n a n

c n =

1 + 4 + 7 + · · · + (3n 2)

= (1 + 0) + (1 + 3) + (1 + 6) + · · · + (1 + 3(n 1))

= n + 0 + 3 + 6 + · · · + 3(n 1)

= n + 3(1 + 2 + 3 + · · · + (n 1))

=

=

n + 3b n1 = n + (n 1)n

2

n(3n 1)

2

.

= 2n + 3(n 1)n

2

c n = n(3n 1)

2

.

= n(2 + 3n 3)

2

n 0 = 1

c 1 = 1 = 2 2 = 1(3 · 1 1)

2

.

c n = n(3n1) (n + 1)

2

n

c n+1 =

=

=

1 + 4 + · · · + (3n 2) +(3(n + 1) 2) = c n + 3n + 1

=c n

n(3n 1)

2

+ 2(3n + 1)

2

(n + 1)(3(n + 1) 1)

2

.

= 3n 2 n + 6n + 2

2

= 3n 2 + 5n + 2

2

= (n + 1)(3n + 2)

2

c n+1 n n + 1

13, 40,

20, 10,

5,

16,

8,

4,

2,

1,

4,

2,

1,

.

 3, 10, 5, 16, 8, 4, 2, 1, . . . 7, 22, 11, 34, 17, 52, 26, 13, 40, 20, 10, 5, 16, 8, 4, 2, 1, . . . 9, 28, 14, 7, 22, 11, 34, 17, 52, 26, 13, 40, 20, 10, 5, 16, 8, 4, 2, 1, . . .

n 4, 2, 1

A B ⇐⇒ B ∨ ¬A.

 ¬ ∨¬ ⇒ A ⇒ B ⇐⇒ B ∨ ¬A

¬(A B) ⇐⇒ (¬A) (¬B).

 ¬ ¬ (¬A) ∧ (¬B) A ∨ B ¬(A ∨ B) ¬(A ∨ B) ⇐⇒ (¬A) ∧ (¬B)

H := A (B C) ⇐⇒ (A B) (A C)

 B ∧ C A ∨ (B ∧ C) A ∨ B A ∨ C (A ∨ B) ∧ (A ∨ C)

G := ((A B) (B C) ) (A C).

=:F

 A ⇒ B B ⇒ C F A ⇒ C G

a, x, y > 0 c

log a (xy) = log a (x) +

log a x = log a (x)

y

log a (x c ) = c

 log a (y) log a (y) log a (x)

ln

xy 7

3

z

2

3

(1),(2)

=

ln x

3 + ln(y 7 ) ln z 2

1

3 (3)

= 1 3 ln(x) + 7 ln(y)

2

3 ln(z)

x, y, z +

log b x = y b y = x b log b x = x,

log a x c = log a x

log a x log b a = log b a log a x

= log b x.

log b a log b a

= 0 a

= 1

log a x = log log b b x a

1 a b log 1 log b 1 = 0 0

f (x) = 1 + sin(3x) 2π sin

3

2π π

2

π

2

+ 2π

3

π

6

+ 2π

3

n n

n n f 2

y
2
1
x
π
π
π
π
− π
− π
− π
2 3
6
6
3
2
3
6 6
3
2

1 + sin(3x)

f (x) = cos( x ) 4π π π + 2πn n 2π + 4πn 4πn n f 1 1

2

y
1
x
−π
π
−1
− cos( x )
2
f (x) = cos(x + π ) = − sin(x) 2π
πn n ∈ 3π + 2πn
π + 2πn n ∈
f 1 −1
2
2
2

f (x) = 2 sin 2 x π πn n

y
1
x
−π
π
− π
π 3π
2 2
2
2
−1
cos(x + π )
2
π
+ πn n ∈ f 2
2
y
2
1
x
−π
π
− π
π 3π
2 2
2
2

2 sin 2 x